Lithium manganate positive electrode material, preparation method thereof and electrochemical device
By using spray coating method to form a lithium phosphate coating layer on the lithium manganate positive electrode material, the problem of capacity attenuation of lithium manganate positive electrode material during high temperature cycle is solved, and its structural stability and cycling performance are significantly improved.
Patent Information
- Application Number
- CN202411938198.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-21
AI Technical Summary
The lithium manganate positive electrode material has severe capacity decayed during high-temperature cycles, which restricts its large-scale promotion.
A uniform lithium phosphate coating layer is formed on the surface of the substrate material of the lithium manganate positive electrode material by spray coating method, and spinel-type lithium manganate matrix material is formed by primary sintering, and secondary sintering is performed to enhance the adhesion of the coating layer.
The lithium ion conductivity, structural stability and cycling performance of lithium manganate positive electrode material is improved, the capacity attenuation and structural collapse in high-temperature cycles are reduced, and its cycle life is extended.
Smart Images

Figure CN119660809A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of new energy materials, and in particular to a lithium manganate positive electrode material, a preparation method thereof, and an electrochemical device. Background Art
[0002] Lithium-ion batteries are increasingly being used in various fields due to their excellent high energy density. The cathode materials of lithium-ion batteries generally use lithium cobalt oxide, ternary materials, lithium manganese oxide and lithium iron phosphate. Among them, lithium manganese oxide cathode materials have become one of the most popular cathode materials due to their high theoretical capacity, abundant raw material reserves and low price.
[0003] However, in practical applications, the capacity of lithium manganese oxide positive electrode materials decays severely during high-temperature cycles. This problem limits the large-scale promotion of lithium manganese oxide positive electrode materials. Summary of the invention
[0004] In view of this, in order to solve at least one of the above technical problems, an embodiment of the present application provides a method for preparing a lithium manganese oxide positive electrode material.
[0005] The embodiments of the present application also provide a lithium manganese oxide positive electrode material obtained by the above-mentioned preparation method of the lithium manganese oxide positive electrode material, and an electrochemical device using the lithium manganese oxide positive electrode material.
[0006] In a first aspect, an embodiment of the present application provides a method for preparing a lithium manganese oxide positive electrode material, comprising: Mixing a lithium source and a manganese-containing oxide to form a mixed material, and sintering the mixed material once to form spinel-type lithium manganate to obtain a matrix material; and The base material is coated with a lithium phosphate solution by spray coating, and the coated base material is subjected to secondary sintering to form a coating layer on the surface of the base material to obtain the lithium manganate positive electrode material.
[0007] In some possible embodiments, the mass percentage of lithium phosphate in the lithium phosphate solution to the matrix material is 0.1 wt % to 10 wt %.
[0008] In some possible embodiments, the spray coating spray speed is 10 rpm ~500 rpm.
[0009] In some possible embodiments, the diameter of the spray-coated nozzle is 0.7 mm to 1.5 mm; and / or The nozzle pressure of the spray coating is 0.05 MPa~1 MPa.
[0010] In some possible embodiments, the step of coating the base material by spray coating further includes: The base material is stirred, and the stirring speed is greater than the spraying speed of the spray coating.
[0011] In some possible embodiments, the spray coating spray speed is 10 rpm ~280 rpm, and the stirring speed is 300 rpm ~800 rpm.
[0012] In some possible embodiments, the primary sintering temperature is 700° C. to 980° C., and the primary sintering time is 8 h to 15 h.
[0013] In some possible embodiments, the temperature of the secondary sintering is 600° C. to 780° C., and the time of the secondary sintering is 8 h to 15 h.
[0014] In some possible embodiments, the manganese-containing oxide includes at least one of MnO2, Mn3O4, Mn2O3 and MnO; and / or The lithium source includes at least one of lithium carbonate and lithium hydroxide.
[0015] In a second aspect, an embodiment of the present application provides a lithium manganese oxide positive electrode material prepared by the aforementioned method for preparing the lithium manganese oxide positive electrode material, wherein the lithium manganese oxide positive electrode material comprises a spinel-type lithium manganese oxide base material and a lithium phosphate coating layer located on at least a portion of the surface of the base material.
[0016] In a third aspect, an embodiment of the present application provides an electrochemical device, which includes a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the positive electrode plate includes a positive electrode active substance, and the positive electrode active substance is the aforementioned lithium manganese oxide positive electrode material.
[0017] Compared with the prior art, the lithium manganese oxide positive electrode material provided in the embodiment of the present application adopts a spray coating method to form a uniform lithium phosphate coating layer on the surface of the base material. First, since lithium phosphate has good lithium ion conductivity, the lithium phosphate coating layer can promote the diffusion and migration of lithium ions in the lithium manganese oxide positive electrode material, thereby improving the charge and discharge efficiency and rate performance of the battery. Secondly, lithium phosphate has a regular tetrahedral structure, which can support the base material, thereby improving the structural stability of the lithium manganese oxide positive electrode material; at the same time, the lithium phosphate coating layer also has good thermal stability. In high-temperature cycles, it effectively reduces the side reactions between the lithium manganese oxide positive electrode material and the electrolyte, reduces the structural collapse of the lithium manganese oxide positive electrode material during the charge and discharge process and the dissolution of active substances, thereby improving the capacity retention rate and cycle life of the lithium manganese oxide positive electrode material. In addition, the lithium phosphate coating layer formed by spray coating has good uniformity, which is beneficial to improving the interface stability of the lithium manganese oxide positive electrode material, and does not require drastic mechanical mixing, which is beneficial to reducing the Mn in the lithium manganese oxide positive electrode material. 3+ Proportion, reduce Mn 3+ Disproportionation and Jiang-Taylor effect improve the stability and mechanical strength of lithium manganese oxide positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 A process flow chart of a method for preparing a lithium manganese oxide positive electrode material provided in one embodiment of the present application.
[0019] Figure 2 A schematic diagram of the structure of an electrochemical device provided in one embodiment of the present application.
[0020] Figure 3 This is a field emission scanning electron microscope image of the lithium manganese oxide positive electrode material in Example 1 of the present application.
[0021] Figure 4 This is a field emission scanning electron microscope image of the lithium manganese oxide positive electrode material in Comparative Example 2 of the present application.
[0022] Figure 5 The charge and discharge curves of the battery prepared with the lithium manganese oxide positive electrode material in Examples 1-4 and Comparative Examples 1-2 of the present application.
[0023] Figure 6 This is a cycle performance diagram of the battery prepared with the lithium manganese oxide positive electrode material in Examples 1-4 and Comparative Examples 1-2 of the present application.
[0024] Figure 7 This is a rate performance diagram of batteries prepared with lithium manganese oxide positive electrode materials in Examples 1-4 and Comparative Examples 1-2 of the present application. DETAILED DESCRIPTION
[0025] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0026] In high temperature cycles, the capacity decay of lithium manganese oxide positive electrode materials is mainly due to the Mn 3+ One is caused by Mn 3+ First, a disproportionation reaction will occur, and second, the Jahn-Teller effect will occur, which will cause the crystal structure to be distorted, the disproportionation reaction to be enhanced, the internal stress of the lithium manganese oxide positive electrode material particles to increase, the lattice to be distorted, and the capacity to decay. The inventors have found that when the surface of spinel lithium manganese oxide is modified by a solid phase method using coating agents such as oxides and fluorides, the coating layer has poor electrical and lithium conductivity, which is not conducive to the transmission of lithium ions, and is not conducive to improving the rate performance and cycle stability of the battery. At the same time, there are also high requirements for the size of the coating agent, and the process is difficult.
[0027] To do this, see Figure 1 As shown, the present application embodiment provides a method for preparing a lithium manganese oxide positive electrode material, which specifically includes the following steps: Step S1, mixing a lithium source and a manganese-containing oxide to form a mixed material, and sintering the mixed material once to form spinel-type lithium manganate to obtain a matrix material.
[0028] In this step, a mixed material is formed by mixing a lithium source and a manganese-containing oxide in a certain ratio, wherein the molar ratio of lithium element in the lithium source to manganese element in the manganese-containing oxide is (0.4-0.6):1. The molar ratio can be 0.4:1, 0.5:1, 0.6:1 or any value within the range of any two of the above values. The molar ratio can further be (0.55-0.595):1.
[0029] In some embodiments, the mixing method may include mixing with a high-speed mixer, stirring or grinding, etc. It is understood that the mixing method includes but is not limited to the above methods. The mixing method is further mixing with a high-speed mixer.
[0030] In some embodiments, the primary sintering temperature is 700°C to 980°C. The primary sintering temperature within the above range can promote grain growth, reduce the number of grain boundaries and grain boundary defects, improve the crystallization quality and stability of the material, and facilitate the formation of a stable spinel phase. The primary sintering temperature can be 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 980°C, or any value within the range of any two of the above values. Further, the primary sintering temperature can be 700°C to 850°C.
[0031] The time of the primary sintering can be 8h~15h, which is conducive to the lithium source and the manganese-containing oxide to fully react to form a matrix material. The time of the primary sintering can be 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h or any value within the range of any two of the above values. The time of the primary sintering can further be 10h~13h.
[0032] In some embodiments, the heating rate of the primary sintering may be 2° C. / min to 3° C. / min, which is beneficial for reducing crystal defects.
[0033] In some embodiments, the primary sintering atmosphere may be an air atmosphere.
[0034] In some embodiments, after the mixed material is sintered once to obtain the matrix material, the matrix material can also be crushed to obtain a powdered matrix material. By crushing, the particle size of the matrix material is reduced, which is conducive to improving the uniformity of subsequent coating. Exemplarily, the particle size D50 of the matrix material can be 5μm~15μm.
[0035] In some embodiments, the manganese-containing oxide includes at least one of MnO 2 , Mn 3 O 4 , Mn 2 O 3 , and MnO, among others.
[0036] In some embodiments, the lithium source may include at least one of lithium carbonate and lithium hydroxide.
[0037] Step S2, coating the base material with the lithium phosphate solution by spray coating, and performing secondary sintering on the coated base material to form a coating layer on the surface of the base material to obtain a lithium manganate positive electrode material.
[0038] Specifically, lithium phosphate is dissolved in water to obtain a lithium phosphate solution, and the lithium phosphate solution is evenly coated on the surface of the base material by spraying. The coated base material is then subjected to secondary sintering, and after cooling, it is dispersed and sieved to obtain a spinel lithium manganese oxide positive electrode material with a lithium phosphate coating layer.
[0039] Compared with solid phase coating, the coating layer formed by spray coating has better uniformity, smoothness, density and adhesion, which is beneficial to improve the interface stability of lithium manganese oxide positive electrode materials. And no drastic mechanical mixing is required, which is beneficial to reduce the Mn content in lithium manganese oxide positive electrode materials. 3+ Proportion, reduce Mn 3+ The disproportionation and Jiang-Taylor effect can be reduced, thereby improving the capacity retention rate and cycle stability of lithium manganese oxide positive electrode materials. However, the surface of the coating layer formed by the dry method is rough, which hinders the transmission of lithium ions and is prone to side reactions with the electrolyte.
[0040] Lithium phosphate as coating: First, lithium phosphate has good lithium ion conductivity, so lithium phosphate as a coating can promote the diffusion and migration of lithium ions in lithium manganese oxide positive electrode materials, thereby improving the battery's charge and discharge efficiency and rate performance. Secondly, lithium phosphate has a regular tetrahedral structure, which can support the matrix material and effectively alleviate the volume change caused by the insertion and deinsertion of lithium ions during the charge and discharge process. It not only enhances the mechanical strength of the lithium manganese oxide positive electrode material, but also reduces the cracks and deterioration caused by uneven stress, thereby improving the structural stability of the lithium manganese oxide positive electrode material. At the same time, the lithium phosphate coating also has good thermal stability. In high-temperature cycles, it effectively reduces the side reactions between the lithium manganese oxide positive electrode material and the electrolyte, reduces the structural collapse of the lithium manganese oxide positive electrode material during the charge and discharge process, and the dissolution of active substances, thereby improving the capacity retention rate and cycle life of the lithium manganese oxide positive electrode material. Therefore, the presence of the phosphate coating improves the structural stability and cycle performance of the lithium manganese oxide positive electrode material.
[0041] In some embodiments, the mass percentage of lithium phosphate in the lithium phosphate solution to the matrix material can be 0.1wt%~10wt%. By controlling the coating amount of lithium phosphate, the thickness of the coating layer can be controlled, which is conducive to forming an effective lithium phosphate coating layer on the surface of the matrix material and balancing the capacity of the lithium manganate positive electrode material and the stability of the coating layer. It can be understood that the coating amount cannot be too high, otherwise it will affect the capacity of the matrix material itself, and the coating amount cannot be too low to form an effective coating layer. Exemplarily, it can be 0.1wt%, 0.5wt%, 1.0wt%, 2.0wt%, 3.0wt%, 4.0wt%, 5.0wt%, 6.0wt%, 7.0wt%, 8.0wt%, 9.0wt%, 10wt% or any value within the numerical range composed of any two of the above values. The mass percentage of lithium phosphate in the lithium phosphate solution to the matrix material can further be 0.2wt%~5wt%.
[0042] Spray coating processes can include: In some embodiments, the spray speed can be 10 rpm to 500 rpm, which is beneficial to improve the coating uniformity. The spray speed can be 10 rpm, 50 rpm, 100 rpm, 200 rpm, 300 rpm, 400 rpm, 500 rpm or any value in the numerical range composed of any two of the above values. The spray speed can further be 10 rpm to 300 rpm.
[0043] In some embodiments, the nozzle opening diameter may be 0.7 mm to 1.5 mm, which is beneficial to improve the fineness and uniformity of the spray, thereby improving the spray effect of the lithium phosphate solution. The nozzle opening diameter may be 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 1.3 mm, 1.5 mm, or any value within a numerical range consisting of any two of the above values. The nozzle opening diameter may further be 0.7 mm to 1 mm.
[0044] In some embodiments, the nozzle pressure is 0.05MPa~1MPa, which is beneficial to improve the atomization effect of the spray and to evenly spray the substrate material with the lithium phosphate solution. The nozzle pressure can be 0.05MPa, 0.08MPa, 0.1MPa, 0.3MPa, 0.5MPa, 0.8MPa, 1MPa or any value within the numerical range composed of any two of the above values. The nozzle pressure can further be 0.06MPa~0.5MPa.
[0045] In some embodiments, the spray speed of the spray coating can be uniform, which is beneficial to improve the uniformity of the coating.
[0046] In the step of coating the base material by spray coating, the base material can be in a tumbling state. For example, the base material is stirred in a high-speed mixer that keeps running at a low speed and is continuously tumbling at a low speed to improve the adequacy and uniformity of the coating.
[0047] The stirring speed can be greater than the spray speed of the spray coating. The stirring and spraying work together to allow the base material to contact the spray droplets in all directions, reducing coating defects caused by uneven spraying or stationary base material, so that the base material can be accurately and efficiently coated. Furthermore, the spray speed of the spray coating can be 10rpm~280rpm, and the stirring speed can be 300rpm~800rpm.
[0048] The temperature of the secondary sintering can be 600°C to 780°C. Within the above temperature range, the uniformity, compactness and bonding strength of the lithium phosphate coating layer with the substrate material can be improved, which is beneficial to improving the coating effect. The temperature of the secondary sintering can be 600°C, 650°C, 700°C, 750°C, 780°C or any value within the range of any two of the above values. The temperature of the secondary sintering can further be 600°C to 650°C.
[0049] The time of the secondary sintering can be 8h~15h, which is conducive to fully sintering to form the coating layer. The time of the secondary sintering can be 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h or any value within the range of any two of the above values. The time of the secondary sintering can further be 9h~12h.
[0050] In some embodiments, the atmosphere of the secondary sintering may be an air atmosphere. Compared with the prior art, the method for preparing the lithium manganese oxide positive electrode material provided in the embodiment of the present application has the following beneficial effects: 1. By using the spray coating method to coat lithium phosphate in the liquid phase, the uniformity, density and adhesion of the lithium phosphate coating layer can be improved, thereby effectively improving the conductivity, structural stability and cycle performance of the lithium manganese oxide positive electrode material.
[0051] 2. By crushing the base material, the particle size and particle morphology of the base material are improved, and the uniformity of the coating is improved.
[0052] 3. The preparation method is simple and efficient, which is conducive to the large-scale production of lithium manganese oxide positive electrode materials and has excellent commercial prospects.
[0053] An embodiment of the present application also provides a lithium manganese oxide positive electrode material prepared by the above-mentioned method for preparing the lithium manganese oxide positive electrode material, wherein the lithium manganese oxide positive electrode material includes a spinel lithium manganese oxide base material and a lithium phosphate coating layer located on at least a portion of the surface of the base material.
[0054] Compared with the prior art, the lithium manganese oxide positive electrode material provided in the embodiment of the present application can promote the diffusion and migration of lithium ions in the lithium manganese oxide positive electrode material because lithium phosphate has good lithium ion conductivity and thermal stability, and effectively reduce the direct contact between the matrix material and the electrolyte. During the charge and discharge process, it can reduce the structural collapse of the lithium manganese oxide positive electrode material and the dissolution of the active material, slow down the Jiang-Taylor effect, and thus improve the conductivity and cycle life of the lithium manganese oxide positive electrode material. In addition, since the spray coating method is used to coat the lithium phosphate in the liquid phase, the lithium phosphate coating layer has the advantages of high uniformity, high density and strong adhesion, which can further improve the conductivity, structural stability and cycle performance of the lithium manganese oxide positive electrode material in a long term.
[0055] See also Figure 2 As shown, an embodiment of the present application also provides an electrochemical device (such as a battery), wherein the electrochemical device 100 includes a positive electrode plate 10, a negative electrode plate 20, a separator 30 and an electrolyte 40, wherein the positive electrode plate 10 includes a positive electrode active material, and the positive electrode active material is the lithium manganese oxide positive electrode material as mentioned above.
[0056] The electrochemical device 100 prepared using the aforementioned lithium manganese oxide positive electrode material has the advantages of high structural stability, high cycle stability and long life, and can be suitable for long-term cyclic use, meeting the requirements for high specific capacity and long cycle life of the electrochemical device 100.
[0057] The above-mentioned lithium manganese oxide positive electrode material, its preparation method and electrochemical device are further described below through specific examples.
[0058] Example 1 Step S1, Mn3O4 and lithium carbonate are mixed by a high-speed mixer according to a molar ratio of lithium element in lithium carbonate to manganese element in Mn3O4 of 0.56:1, and then sintered and crushed in an air atmosphere. The primary sintering temperature is 745°C, the primary sintering time is 12 hours, and a spinel lithium manganate matrix material is obtained, and the particle size D50 of the matrix material is 7 μm.
[0059] Step S2, dissolving lithium phosphate in water to obtain a lithium phosphate solution, wherein the mass percentage of lithium phosphate in the matrix material is 0.1wt%, and then spraying the lithium phosphate solution uniformly on the surface of the matrix material at a speed of 150rpm with a nozzle diameter of 1mm and a nozzle pressure of 0.08MPa, wherein the matrix material is stirred and turned in a high-speed mixer running at a low speed of 400rpm, and the coated material is secondary sintered in an air atmosphere at a temperature of 700°C for 10h to obtain a spinel lithium manganate positive electrode material coated with lithium phosphate.
[0060] Example 2 The difference from Example 1 is that in step S2, the temperature of the secondary sintering is 600° C. The other steps are basically the same as those in Example 1, please refer to Example 1.
[0061] Example 3 The difference from Example 1 is that in step S2, the mass percentage of lithium phosphate in the matrix material is 0.2 wt %. The other steps are basically the same as Example 1, please refer to Example 1.
[0062] Example 4 The difference from Example 1 is that in step S2, the mass percentage of lithium phosphate in the matrix material is 10wt%. The other steps are basically the same as Example 1, please refer to Example 1.
[0063] Comparative Example 1 Step S1, Mn3O4 and lithium carbonate are mixed in a high-speed mixer at a molar ratio of 0.56:1 between lithium element in lithium carbonate and manganese element in Mn3O4, and then sintered once in an air atmosphere. The primary sintering temperature is 745°C, and the primary sintering time is 12 hours, to obtain a spinel lithium manganate positive electrode material without a coating layer.
[0064] Comparative Example 2 Step S1, Mn3O4 and lithium carbonate are mixed in a high-speed mixer according to a molar ratio of lithium element in lithium carbonate to manganese element in Mn3O4 of 0.56:1, and then sintered once in an air atmosphere. The primary sintering temperature is 745°C, and the primary sintering time is 12 hours to obtain a spinel lithium manganate matrix material.
[0065] Step S2, solid-phase mixed coating of lithium phosphate and matrix material, wherein the mass percentage of lithium phosphate in the matrix material is 0.1wt%, and the coated material is secondary sintered in an air atmosphere at a temperature of 700°C for 10 hours to obtain a spinel lithium manganese oxide positive electrode material coated with lithium phosphate.
[0066] The following tests were performed on the lithium manganese oxide positive electrode materials obtained in Examples 1-4 and Comparative Examples 1-2.
[0067] Test method: 1. Field emission scanning electron microscope (FESEM) test: The JSM-7610FPLUS field emission scanning electron microscope is used. This instrument has high-resolution imaging capabilities and can clearly observe the microscopic morphology and structural characteristics of the positive electrode material. The acceleration voltage is 2.00kV and the magnification is 30,000 times.
[0068] 2. Electrochemical performance test: Use button cells for electrical performance test, with a test voltage of 3.0V~5.0V; weigh the above-mentioned positive electrode materials, polyvinylidene fluoride (PVDF), and conductive agents (such as acetylene black or conductive carbon black) in a certain proportion, and add an appropriate amount of NMP to make a slurry. Then, evenly coat the slurry on aluminum foil, vacuum dry it at 115℃±5℃ / 8h, compact it, cut it into discs, and use metal lithium sheets as negative electrode materials. Finally, transfer them to the glove box and assemble them into CR2025 button cells. Use the LAND battery test system for constant current charge and discharge tests.
[0069] (I) Charge and discharge performance test: The charge and discharge capacity of the battery made of lithium manganese oxide positive electrode material is measured at an operating voltage range of 3.0V~4.3V and a current density of 0.1C / 0.1C.
[0070] (II) Cycle performance test: The operating voltage range is 3.0V~4.3V, the temperature is 45℃, and the current density is 0.5C / 0.5C for 50 cycles to measure the capacity retention rate of the battery made of lithium manganese oxide positive electrode material.
[0071] (III) Rate performance test: The test operating voltage range is 3.0V~4.3V, the temperature is 25℃, and the discharge capacity at current density of 0.1C and 1C.
[0072] The relevant test results of Examples 1-4 and Comparative Examples 1-2 are shown in Table 1.
[0073] The above results show: The field emission scanning electron microscopy results of the lithium manganese oxide positive electrode material prepared in Example 1 are as follows Figure 3 As shown, the field emission scanning electron microscopy results of the lithium manganese oxide positive electrode material prepared in Comparative Example 2 are as follows Figure 4 As shown. Figure 3 and Figure 4 It can be seen that compared with the solid phase coating of Comparative Example 2, Example 1 adopts spray coating, and the surface of the obtained lithium manganese oxide positive electrode material is more uniform and clean, which is beneficial to improving the interface stability of the lithium manganese oxide positive electrode material.
[0074] The charge and discharge curves of the batteries prepared with lithium manganese oxide positive electrode materials in Examples 1-4 and Comparative Examples 1-2 of the present application are as follows: Figure 5 As shown. Figure 5 As shown, from the perspective of capacity, the platform between 3.0 and 3.4 V in Comparative Example 2 is wider, indicating that the Mn 3+ The content is more than that of Example 1-4, resulting in a decrease in capacity, and the cycle performance of the lithium manganese oxide positive electrode material will deteriorate due to the disproportionation reaction and the Jan-Taylor effect. This is because the lithium manganese oxide positive electrode material in Example 1-4 is prepared by spray coating method rather than drastic solid phase coating, forming a uniform lithium phosphate coating layer, reducing the Mn in the lithium manganese oxide positive electrode material. 3+ The content of lithium manganese oxide improves the structural stability of the lithium manganese oxide positive electrode material and reduces the dissolution of active substances.
[0075] The cycle performance of the battery prepared with the lithium manganese oxide positive electrode material in Examples 1-4 and Comparative Examples 1-2 of the present application is as follows: Figure 6 As shown in Table 1 and Figure 6 As known, at high temperature, the cycle stability of Examples 1-4 is significantly better than that of Comparative Examples 1-2, which indicates that the uniform lithium phosphate coating layer in Examples 1-4 improves the thermal stability and cycle stability of the lithium manganese oxide positive electrode material.
[0076] The rate performance of the battery prepared with the lithium manganese oxide positive electrode material in Examples 1-4 and Comparative Examples 1-2 of the present application is as follows: Figure 7 As shown in Table 1 and Figure 7 As known, compared with Comparative Examples 1-2, the rate performance of the lithium manganese oxide positive electrode material of Examples 1-4 is improved, which is because the uniform coating of lithium phosphate improves the conductivity and lithium ion transfer rate of the lithium manganese oxide positive electrode material.
[0077] It can be seen that the lithium phosphate is uniformly coated on the surface of the lithium manganese oxide matrix material by the spray coating method, so that the lithium manganese oxide positive electrode material can show ideal capacity density, cycle stability, rate performance and thermal stability.
[0078] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.
Claims
1. A method for preparing a lithium manganese oxide positive electrode material, characterized in that: include: Mixing a lithium source and a manganese-containing oxide to form a mixed material, and sintering the mixed material once to form spinel-type lithium manganate to obtain a matrix material; as well as The base material is coated with a lithium phosphate solution by spray coating, and the coated base material is subjected to secondary sintering to form a coating layer on the surface of the base material to obtain the lithium manganate positive electrode material.
2. The method for preparing the lithium manganate positive electrode material according to claim 1, characterized in that: The mass percentage of lithium phosphate in the lithium phosphate solution to the matrix material is 0.1wt%-10wt%.
3. The method for preparing the lithium manganate positive electrode material according to claim 1, characterized in that: The spray coating spray speed is 10rpm~500rpm.
4. The method for preparing the lithium manganate positive electrode material according to claim 1, characterized in that: The nozzle pressure of the spray coating is 0.05MPa~1MPa; and / or The diameter of the spray-coated nozzle is 0.7 mm to 1.5 mm.
5. The method for preparing the lithium manganate positive electrode material according to claim 1, characterized in that: The step of coating the base material by spray coating also includes: The base material is stirred, and the stirring speed is greater than the spraying speed of the spray coating.
6. The method for preparing the lithium manganate positive electrode material according to claim 5, characterized in that: The spray coating spray speed is 10rpm~280rpm, and the stirring speed is 300rpm~800rpm.
7. The method for preparing the lithium manganate positive electrode material according to claim 1, characterized in that: The primary sintering temperature is 700°C to 980°C, and the primary sintering time is 8h to 15h; and / or The temperature of the secondary sintering is 600° C. to 780° C., and the time of the secondary sintering is 8 h to 15 h.
8. The method for preparing the lithium manganate positive electrode material according to claim 1, characterized in that: The manganese-containing oxide comprises at least one of MnO2, Mn3O4, Mn2O3 and MnO; and / or The lithium source includes at least one of lithium carbonate and lithium hydroxide.
9. A lithium manganate positive electrode material, characterized in that: The lithium manganese oxide positive electrode material is prepared by the preparation method of the lithium manganese oxide positive electrode material according to any one of claims 1 to 8, wherein the lithium manganese oxide positive electrode material comprises a spinel lithium manganese oxide base material and a lithium phosphate coating layer located on at least a portion of the surface of the base material.
10. An electrochemical device, characterized in that: The electrochemical device comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a positive electrode active material, and the positive electrode active material is the lithium manganate positive electrode material as described in claim 9.